A study of service recovery actions by TM Point Kuala Krai / Nadhrathul Ain Ibrahim - Ibrahim, Nadhrathul Ain (2012)
Service recovery action is one of the strategies that is implemented by many companies to recover their service failure toward their customers. The researcher has studied the service recovery action that are provided by TM Point Kuala Krai. There are three strategies involved in this research which are distributive justice, processing justice and interactive justice. The objective of this study is to identify the factors that influence service recovery actions by TM Point Kuala Krai. Besides that, this study is to give suggestions and recommendations to TM Point Kuala Krai on how to improve their service recovery strategy. This study takes an exploratory approach. Exploratory research is conducted by the researcher to obtain greater understanding of a concept or to help crystallize the definition of a problem. The researcher is used non probability technique which it is convenient technique. Convenient technique is the least expensive and least time consuming of all sampling techniques. It is also easy to measure (Malhotra, 2007). Data were gathered from the questionnaires which are distributed to 103 respondents of TM Point Kuala Krai. The data are analyzed by using SPSS through the frequency analysis, reliability test, hypothesis testing and correlation coefficient analysis. From the analysis, the researcher found that distributive justice, interactive justice and processing justice have a significant relationship with the service recovery action provided by TM Point Kuala Krai. From the findings, it shows that distributive justice is the most important factor because it has the strongest correlation than the other factors with service recovery. As a conclusion, the researcher has also stated several recommendations. It is a great pleasure if TM Point Kuala Krai evaluates the suggestions from the respondents and the researcher